2012
DOI: 10.1007/s00128-011-0516-4
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons at Different Crossroads in Zagreb, Croatia

Abstract: Polycyclic aromatic hydrocarbons (PAHs) were measured in the PM(10) particle fraction collected at two different measuring sites in Zagreb, Croatia. In summer, concentrations of all PAHs at both sites were low. In winter, mass concentrations of all PAHs measured at southern site were much higher than those at north. Contents of all PAHs in the PM(10) particle fraction were much lower in summer than that in the winter period. For example, average content of BaP in PM(10) in summer was 2.26 ng/mg at site A and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Mass concentrations of ten PAHs bound to the PM 10 , PM 2.5 , and PM 1 particle fraction measured in this study, as well as ΣPAH showed characteristic variations with the highest values during winter (heating season). Šišović et al [ 40 ], Godec et al [ 43 ], and Jakovljević et al [ 41 ] were determined the similar seasonal differences at the same location as in this study, but their studies were carried out in 2008, 2010, and 2010/2011, respectively. However, all of these studies were limited only to the PM 10 particle fraction.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Mass concentrations of ten PAHs bound to the PM 10 , PM 2.5 , and PM 1 particle fraction measured in this study, as well as ΣPAH showed characteristic variations with the highest values during winter (heating season). Šišović et al [ 40 ], Godec et al [ 43 ], and Jakovljević et al [ 41 ] were determined the similar seasonal differences at the same location as in this study, but their studies were carried out in 2008, 2010, and 2010/2011, respectively. However, all of these studies were limited only to the PM 10 particle fraction.…”
Section: Discussionsupporting
confidence: 62%
“…After collection, samples were wrapped in aluminium foil and kept in a deep freezer at −18 °C until analysis [ 40 ]. Filters were extracted with a solvent mixture of toluene and cyclohexane (7:3) in an ultrasonic bath for one hour, separated from undissolved parts by centrifugation (10 min, 3000 rpm), and evaporated to dryness in a mild stream of nitrogen at 30 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The finding was corroborated by the differences in the linear correlation coefficients calculated between the concentrations of specific PAHs, the PAH sum and PM1 for the points and seasons ( Figure 5). In the non-heating season in UT, RB and UB, there were high values of correlations between the concentrations of heavier PAHs (i.e., BghiP or DBA), which confirmed the dominant influence of the PAH emission from traffic sources [10,18,20,21]. It seems that due to the lack or to the significant reduction of emissions from other sources, traffic and industry (including energy production) were dominant sources of PAHs in the air of southern Poland.…”
Section: Resultsmentioning
confidence: 70%
“…The south station is in a traffic area and the contribution of six-ringed PAHs was pronounced much more than at the north station located in an urban background with domestic heating as the dominant source of PAHs that lead to a higher contribution of four-ringed PAHs. 11,12 At all locations, DahA had the lowest average mass concentrations; values ranged from 0.005 to 2.435 ng m −3 at Zagreb's south, from 0.005 to 0.443 ng m −3 at Zagreb north, and from the detection limit to 0.093 ng m −3 at Martinska. In order to determine partial differences between the measuring sites for all PAHs, non-parametric Kruskal-Wallis ANOVA and post-hoc multiple comparisons (by Siegel and Castellan) tests were used.…”
mentioning
confidence: 97%
“…PAHs were separated by an Eclipse PAH stainless steel column (100 × 4.6 mm). The mobile phase was a mixture of water and acetonitrile (40 : 60), [11][12][13] Average mass concentrations of specific PAHs at Martinska and Zagreb, for the period February -July 2019, are presented in Fig. 2.…”
mentioning
confidence: 99%